Better Together: Association With ‘Candidatus Liberibacter Asiaticus’ Increases the Reproductive Fitness of Its Insect Vector, Diaphorina citri (Hemiptera: Liviidae) - Pelz-Stelinski, K. S. (Ann Entomol Soc Am, 2016)
The duration of the evolutionary association between a pathogen and vector can be inferred based on the strength of their mutualistic interactions. A well-adapted pathogen is likely to confer some benefit or, at a minimum, exhibit low pathogenicity toward its host vector. Coevolution of the two toward a mutually beneficial association appears to have occurred between the citrus greening disease pathogen, Candidatus Liberibacter asiaticus (Las), and its insect vector, the Asian citrus psyllid, Diaphorina citri (Kuwayama). To better understand the dynamics facilitating transmission, we evaluated the effects of Las infection on the fitness of its vector. Diaphorina citri harboring Las were more fecund than their uninfected counterparts; however, their nymphal development rate and adult survival were comparatively reduced. The finite rate of population increase and net reproductive rate were both greater among Las-infected D. citri as compared with uninfected counterparts, indicating that overall population fitness of infected psyllids was improved given the greater number of offspring produced. Previous reports of transovarial transmission, in conjunction with increased fecundity and population growth rates of Las-positive D. citri found in the current investigation, suggest a long evolutionary relationship between pathogen and vector. The survival of Las-infected adult D. citri was lower compared with uninfected D. citri, which suggests that there may be a fitness trade-off in response to Las infection. A beneficial effect of a plant pathogen on vector fitness may indicate that the pathogen developed a relationship with the insect before secondarily moving to plants.